2021
DOI: 10.3390/ma14195807
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Micro-Scale Strength Properties of Coals Susceptible to Outburst Caused by Changes in Degree of Coalification

Abstract: Coals from the south-western part of the Upper Silesian Coal Basin have a strong outburst susceptibility. The objective of this study was to identify the influence of coalification degree on methane sorption and micro scale strength properties of 24 coals from Jastrzębie Zdrój. Coal samples showed a reflectance Ro between 0.98 and 1.25%. Sorption measurements were carried out by gravimetric method. Sorption capacities were determined at mean deposit temperature of 35 °C. Using the unipore model and solution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Research by the author and other researchers showed a reduction in the sorption capacity of carbon in relation to CH 4 [17]. Both in the case of sorption capacity and the effective diffusion coefficient, the dominant factor influencing the nature of the variability of the mentioned parameters with depth was the degree of coalification [17][18][19]. In the depth range from approximately 680 m to 860 m, the impact of temperature sorption properties was small compared to the coalification degree of the coal substance.…”
Section: Introductionmentioning
confidence: 86%
“…Research by the author and other researchers showed a reduction in the sorption capacity of carbon in relation to CH 4 [17]. Both in the case of sorption capacity and the effective diffusion coefficient, the dominant factor influencing the nature of the variability of the mentioned parameters with depth was the degree of coalification [17][18][19]. In the depth range from approximately 680 m to 860 m, the impact of temperature sorption properties was small compared to the coalification degree of the coal substance.…”
Section: Introductionmentioning
confidence: 86%
“…Based on the analysis of the literature, it can be stated that the petrography of coal has a significant influence on the course of sorption processes in its structure. The literature describes the dependence of the maceral composition and the degree of coalification on the course of diffusion and sorption processes [19,21,22,31,48,[56][57][58]. The diffusivity of hard coal is related to both pore size distribution and porosity in terms of macroscopic equation.…”
Section: Sorption Analysismentioning
confidence: 99%
“…In the oil and gas industry, this data is required, among other things, for assessing the rocks' capacity to accumulate crude oil or natural gas [2,3]. The porosity of rocks is a crucial parameter in geological and geophysical studies [4], aiding in determining the structural composition and properties of rocks [5] and describing the adsorption parameters of rocks [6][7][8][9]. Porosity analyses are instrumental in hydrogeological issues, such as the ability of groundwater to move in underground water reservoirs, water resource management, and source water protection [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Basic petrographic analyses of rocks are usually conducted using polarizing microscopes [8,25,34,35]. To expand the methodology, X-ray analyses, SEM, EDS, etc., are also employed.…”
Section: Introductionmentioning
confidence: 99%